2020
DOI: 10.3390/w12041110
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Crops Grown under High Soil Water Availability in Mediterranean Greenhouses

Abstract: The soil water availability of six vegetable crop cycles, irrigated with water of 0.4 dS m−1 electrical conductivity, was modified by varying the irrigation frequency in typical Mediterranean greenhouses at SE Spain. The soil matric water potential (SMP) in the middle of the loamy soil layer where most roots usually grow was maintained between −10 and −20 kPa (H), −20 and −30 kPa (C), and −30 and −50 kPa (L) for the crops grown under high, conventional and low soil water availability, respectively, while the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Létourneau et al [36] improved yields of strawberry crops (6.2%) with a soil matric potential of −15 kPa to −20 kPa. However, the results obtained in this study are in disagreement with the results obtained by Bonachela et al [38] who affirm that fruit-vegetable greenhouse crops can be irrigated under a relatively wide range of SMP values without significantly affecting their yields. This statement would be valid in the context that these authors study (experiments are not fully comparable), since they apply the same volume of irrigation water in all treatments (in the treatment of high availability of water in the soil and in the treatment of low availability of water in the soil) considering that the high or low availability of water in the soil is associated with the SMP before irrigation.…”
Section: Fv Effectcontrasting
confidence: 99%
“…Létourneau et al [36] improved yields of strawberry crops (6.2%) with a soil matric potential of −15 kPa to −20 kPa. However, the results obtained in this study are in disagreement with the results obtained by Bonachela et al [38] who affirm that fruit-vegetable greenhouse crops can be irrigated under a relatively wide range of SMP values without significantly affecting their yields. This statement would be valid in the context that these authors study (experiments are not fully comparable), since they apply the same volume of irrigation water in all treatments (in the treatment of high availability of water in the soil and in the treatment of low availability of water in the soil) considering that the high or low availability of water in the soil is associated with the SMP before irrigation.…”
Section: Fv Effectcontrasting
confidence: 99%
“…Consequently, the results of experiments based on Θ in a particular soil type are difficult to generalize to different soil types. To circumvent this problem, an increasing number of recent experiments have controlled the level of plant water stress by controlling and monitoring the soil Ψm [40][41][42]. However, the water-stress threshold values of Ψm varies depending on soil properties and the plant type.…”
Section: Water Stress Controlmentioning
confidence: 99%
“…Valença et al [43] indicated that Ψm ranging from −40 to −120 hPa caused water stress for papaya, but not for lettuce. For vegetable crops growing in a loamy sand, Bonachela et al [40] considered −100 to −200 hPa, −200 to −300 hPa and −300 to −500 hPa as high, conventional and low soil water availability, respectively. For an experiment in which maize plants were grown on a sandy material for a short time, Ahmed et al [44] set the Ψm (during 16 days) to −20 to −30 hPa to get non-stressing conditions, when Dowd et al [41] set the Ψm (during 9 days) to −1,000 hPa and −3,000 hPa for non-stressing and mildly stressing conditions, respectively.…”
Section: Water Stress Controlmentioning
confidence: 99%